1. ## Simplifying Trig Expressions

cot^2x - cot^2x(cos^2x)

secx - (cosx/1+sinx)

2. Originally Posted by nichole23
cot^2x - cot^2x(cos^2x)

secx - (cosx/1+sinx)
Hi nichole23,

$\displaystyle \cot^2 x-\cot^2 x(\cos^2 x)=\cot^2 x(1-\cos^2 x)=\frac{\cos^2 x}{\sin^2 x}\left(\sin^2 x\right)=\cos^2 x$

-----------------------------------------------------------------------

$\displaystyle \sec x-\frac{\cos x}{1+\sin x}=$

$\displaystyle \frac{1}{\cos x}-\frac{\cos x}{1+\sin x}=$

$\displaystyle \frac{1+\sin x-\cos^2 x}{\cos x(1+\sin x)}=$

$\displaystyle \frac{1-\cos^2 x+\sin x}{\cos x(1+\sin x)}=$

$\displaystyle \frac{\sin^2 x+\sin x}{\cos x(1+\sin x)}=$

$\displaystyle \frac{\sin x(\sin x+1)}{\cos x(1+\sin x)}=$

$\displaystyle \frac{\sin x}{\cos x}=$

$\displaystyle \tan x$

3. Originally Posted by nichole23
cot^2x - cot^2x(cos^2x)

secx - (cosx/1+sinx)
Here's the first one:

$\displaystyle cot^2 x - cot^2x(cos^2 x)$

$\displaystyle cot^2 x(1- cos^2 x)$

$\displaystyle cot^2 x(sin^2 x)$

You should be able to complete the rest from here?

4. Got beaten to it